Enteral Feeding in Patients With Open Abdomen and Negative Pressure Therapy: A Propensity Score Analysis - Laurent Petit; Nicolas Faure; Bruno Pereira; Vincent Dubuisson; Xavier Berard; Xavier Berard; Matthieu Biais; Matthieu Biais; Cédric Carrié (Journal of Abdominal Wall Surgery)
IntroductionIn critically ill surgical patients treated with open abdomen and negative pressure therapy (OA/NPT), the association between nutritional support and clinical outcome is still controversial. The main objective of this study was to assess the effect of enteral nutritional support during the acute phase (i.e., the first 7 days) on clinical outcome (abdominal wall closure rate or fistula formation) in critically ill surgical patients treated by OA/NPT.MethodsOver a 5-year period, every critically ill patient who underwent nutritional support while treated by OA/NPT was retrospectively included. The main study outcome was a composite criterion, defined as delayed abdominal closure ≥8 days and/or secondary abdominal complications (secondary anastomotic leak, intra-abdominal abscess and fascial dehiscence). Inverse probability of treatment weight (IPTW) was derived from a propensity score model. Multivariable logistic regression was used to test the association between clinical outcome and different modalities of nutritional support (enteral nutrition vs. nil per os during the first week after OA/NPT, early vs. late enteral nutrition, normal vs. low caloric/protein intake).ResultsOver the study period, 171 patients were included and 50% underwent delayed abdominal closure and/or secondary abdominal complications. The rate of delayed abdominal closure or secondary abdominal complications was significantly lower in patients who received enteral nutrition versus those who remained nil per os (40% vs. 61%, p = 0.007), with an IPTW-adjusted OR of poor clinical outcome of 0.49 [95%CI: 0.25–0.98]. There was no other statistical association between modalities of nutritional support and the study outcome.ConclusionIn critically ill patients with OA/NPT, the use of enteral feeding within 7 days after surgery was associated with better clinical outcome. Further studies are mandatory to better define the adequate timing for enteral feeding, the energy needs and the protein requirements during the acute phase after OA/NPT.